Sketching the Tactical Position and Maritime Connectivity of Bengal with Malay Archipelago (321 BCE-750 CE) - Akhtar, Sharmin (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
This study examines the geographical and strategic proximity of Bengal and the interplay between the Bengal and Southeast Asian regions which two entities had a linkage and a great bonding from 321 BCE to 750 CE concerning maritime activities. At that time, Southeast Asia; mainly the Malay Archipelago was known as the Golden Chersonese. Despite having infinite reciprocal geographical and maritime significance, their tactical positions and strategic factors that impacted inter-linkages are seriously marginalised and infrequently looked at from the historical perspective. The study adopts historical research method in analysing the accounts of ancient Greek-Roman geographers and Chinese travellers, ancient texts, and archaeological documents qualitatively to unfold the contextual geographical factors between these two regions. The findings of this study show the strategic proximity of Bengal and its role in creating linkages with Southeast Asia through ports and maritime connectivity. It also demonstrates the socio-cultural impacts on the Southeast Asian regions created by the Bengal’s contacts during the ancient period. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 123-143